Youth revelation of social media on multiculturalism and cultural integration in Indonesia - Muhammad Saud; Abdullah Ibrahim; Asia Ashfaq (Social Sciences and Humanities Open)
This study delves into the intricate youth dynamics of multiculturalism and cultural integration among Indonesian indigenous and non-indigenous identities. This cross-cultural research examines the behaviour of the youth using social media to explore cultural integration. The aim is to investigate three important factors: cultural diversity practices, identity formation and intragroup relations among identities. Indonesia's rich assets of ethnicities, languages, and traditions serve as engaging networks for examining youth experiences and perceptions of multiculturalism. It also elucidates the challenges and opportunities inherent in Indonesia's pluralistic society, which includes discrimination, prejudice, and interethnic stress. The present study applied the quantitative research design, as youth multiculturalism has become a critical area of sociological inquiry, yet empirical studies often lack methodological clarity in examining its complexities. The findings reveal that the youth in Indonesia are more eager to contribute to the nationalism concept of 'Pancasila' among both indigenous and non-indigenous communities. Thus, the youth's exposure to Multiculturalism is increasing, and it also promotes cultural integration among other identities. The study sheds light on the multifaceted dimensions of multiculturalism and social networks among youth from diverse identities and research areas in Indonesia.